Mitotane-Induced Hyperlipidemia: A Retrospective Cohort Study - Hassan Shawa; Ferhat Deniz; Hadil Bazerbashi; Mike Hernandez; Rena Vassilopoulou-Sellin; Camilo Jimenez; Mouhammed Amir Habra (International Journal of Endocrinology)
Limited data are available about mitotane-nduced hyperlipidemia. We retrospectively analyzed lipid data in 38 patients with adrenocortical carcinoma (ACC) who received mitotane therapy with emphasis on HDL cholesterol (HDL-c) and clinical predictors of lipid changes. At baseline, the mean levels of HDL-c, LDL-c, and triglycerides were 53.3 mg/dL, 114.4 mg/dL, and 149 mg/dL, respectively. HDL-c, LDL-c, and triglyceride concentrations significantly increased with mitotane therapy to a mean HDL peak (HDL-P) of 86.3 mg/dL (P<0.001), a mean LDL peak of 160.1 mg/dL (P<0.001), and a mean triglyceride peak (Tg-P) of 216.7 mg/dL (P=0.042). HDL-P positively correlated with mitotane concentration (r=0.52,P<0.001), while LDL-P levels and Tg-P did not. Gender, body mass index, cortisol overproduction, baseline levels of HDL-c, and triglyceride did not predict change in HDL-c. Similar changes were noticed in subgroup analysis after excluding patients who were using lipid-lowering agents. In conclusion, in ACC patients, mitotane caused significant increases in HDL-c that may counteract the deleterious atherosclerotic effects of LDL-c and Tg rise. Understanding the mechanism of HDL change may lead to the discovery of novel HDL-c-elevating drugs.